Analisis Faktor Dominan yang Mempengaruhi Keselamatan Kapal Tugboat - Mega Kariya Imani; Andar Sri Sumantri; Retno Mulatsih (Indonesian Maritime Researchers and Lecturers, 2025)
Ship safety is critical, particularly for operations involving tugboats in busy maritime environments like Cirebon Port, Indonesia.1 Despite strict regulations, annual safety targets are often unmet, prompting the need to assess key influencing factors.1 This study investigates the partial influence of four independent variables—Harbor Master's Role (X_1), Ship Seaworthiness (X_2), Ship Crew (X_3), and Shipping Navigational Aids (X_4)—on Tugboat Safety (Y) at Cirebon Port.1 Employing an associative quantitative method, data were collected via questionnaires distributed to 104 tugboat crew members (N=104).1 Multiple linear regression analysis revealed that all four variables have a positive and significant influence on Ship Safety (Y) (all t_hitung > t_tabel (1.984) and Sig. < 0.05).1 The variable Ship Crew (X_3) was found to be the most dominant factor, exhibiting the highest influence (β=0.352, t_hitung=4.160), confirming the pivotal role of human resources and competence in maritime safety.1 The regression model explained 50.1% of the variation in Ship Safety (Y) (Adjusted R^2 = 0.501), with the remaining 49.9% attributed to external factors, such as unpredictable weather and external policies (Suryani et al., 2018). Managerial implications recommend prioritizing the training and certification of crew members and rigorously enforcing Ship Seaworthiness checks, specifically regarding expired safety equipment.